2000
DOI: 10.3928/1081-597x-20000901-06
|View full text |Cite
|
Sign up to set email alerts
|

Pain After Epithelial Removal by Ethanol-assisted Mechanical Versus Transepithelial Excimer Laser Debridement

Abstract: PURPOSE: To compare subjective pain responses between two techniques of epithelial removal prior to photorefractive keratectomy (PRK) treatment: ethanol-soaked pledget with mechanical debridement of the epithelium versus excimer laser transepithelial ablation. METHODS: Nine patients underwent bilateral PRK. Each had the epithelium in one eye debrided by placing a pledget soaked in 20% ethanol on the cornea for 2 minutes followed by gentle scraping with a blade. The epithelium in the other eye was rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 10 publications
2
26
0
3
Order By: Relevance
“…In the t-PRK group, for all measurements at postoperative days 1 and 3, the scores were lower than in the mechanical PRK group. However Kanitkar et al [52] found that pain after epithelial removal by the ethanol-assisted mechanical technique was lower than transepithelial excimer LASER debridement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the t-PRK group, for all measurements at postoperative days 1 and 3, the scores were lower than in the mechanical PRK group. However Kanitkar et al [52] found that pain after epithelial removal by the ethanol-assisted mechanical technique was lower than transepithelial excimer LASER debridement.…”
Section: Discussionmentioning
confidence: 97%
“…The idea of considering t-PRK as a main treatment option was proposed in 1998 [35]. However, the idea was not proven until 2007 [36,37]. In 2007, t-PRK treatment provided better results than LASIK, LASEK, and epi-LASIK surgeries, phototherapeutic keratectomy mode for epithelial debridement and stromal ablation mode were used for the treatment [38].…”
Section: Discussionmentioning
confidence: 98%
“…At all postoperative intervals, mechanical removal of the epithelium tended to yield better results than laser epithelium removal. In 2000, Kanitkar et al 16 reported 9 patients who had bilateral PRK using the Visx S3 laser, with 1 eye deepithelialized with PTK and the fellow eye deepithelialized with alcohol. All eyes healed within 3 days with no difference in healing time between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The use of alcohol as an alternative to mechanical debridement has been assessed, as has preservation of the epithelium as a flap (laser-assisted sub-epithelial keratectomy [LASEK] and Epi-LASIK) 4. Another alternative is transepithelial PRK, where epithelial removal is generally carried out with laser phototherapeutic (PTK) ablation, followed by a stromal laser refractive ablation 58. Transepithelial PRK has several advantages, including no instrument contact with the eye, reduced intervention time, and the potential to minimize the size of an epithelial defect to that required for stromal ablation, as well as the avoidance of alcohol and, thus, potential toxicity.…”
Section: Introductionmentioning
confidence: 99%